Numerical analysis of energy loss in a laboratory-scale tandem double cylinders based on entropy production method - Han Liang; Zhumei Luo; Tao Guo; Juan Duan; Jun Li; Xia Ren; Ye Li (AIP Advances)
Vortex-induced vibration (VIV) to capture low-velocity water current energy has broad application prospects. To utilize low-velocity hydrokinetic energy on a large scale, the energy capture structure should be composed of multiple cylinders. In this paper, the hydrokinetic energy harvested from low-velocity water current with two three-dimensional cylinder oscillators in tandem arrangement driven by VIV is simulated in the range of reduced velocity Ur = 2–13. The entropy production theory is applied to evaluate energy loss quantitatively and analyze the correlation between energy dissipation and hydrokinetic energy capture of upstream and downstream cylinders. Combined with Liutex’s third-generation vortex identification method, the correlation between vortex coupling and evolution process and energy loss of the two cylinders is obtained. The results show the following: (1) The amplitude response of both upstream and downstream cylinders shows three distinct response branches. (2) The maximum energy capture efficiencies of the upstream and downstream cylinders are 40.53% and 37.71%, respectively. Peak power and efficiency are observed primarily in the upper branch, diminishing after transitioning to the lower branch and eventually approaching zero. (3) The main loss of turbulent entropy production (EPTD) caused by turbulence dissipation, collision, and vortex accounts for the largest proportion, up to more than 99%, while the entropy production rate caused by direct dissipation is close to 0 and can be negligible. In the lower branch, the entropy production loss increases exponentially, resulting in a significant decrease in the captured hydrokinetic energy PVIV and efficiency ηVIV of the two cylinders. The local entropy production rate caused by wall shear stress is larger in the process of vortex formation and smaller in the process of vortex shedding. The variations in the entropy production rate caused by wall shear stress reflect the strength of the interaction between the fluid and the structure, consequently reflecting the ability of hydrokinetic energy harvested by the upstream and downstream oscillators.